The effect of language awareness approach on intermediate learners’ use of collocations in essay writing - Vo, Tai (English Education Department, Universitas Islam Indonesia, 2026)
Vocabulary learning increasingly highlights formulaic sequences, particularly collocations, which are essential but persistently difficult for language learners. Traditional instruction often overlooks collocational use in writing, and existing language awareness research focuses mainly on grammar and passive vocabulary gains, with limited evidence regarding metalanguage’s role in collocation use. Addressing these gaps, the present study investigates the effect of the Language Awareness Approach on intermediate learners’ use of collocations in essay writing, as well as their perspectives toward this approach. Adopting a mixed-methods explanatory sequential design, the study employed quasi-experimental design, with two classes comprising 50 students assigned as an experimental group and a control group. Pre- and post-tests were used to assess changes in collocational performance, while questionnaires and semi-structured interviews were then employed so that learners’ perspectives on the approach can be captured. The quantitative results revealed that although both groups improved, the experimental group demonstrated clearer gains in the accuracy and variety of lexical collocations. Qualitative findings revealed strong affective, cognitive, and social engagement, with these dimensions reinforcing each other. Two further patterns refined the picture: the value of metalanguage was conditional rather than categorical, and learners’ reliance on teacher guidance suggests that the approach functions as guided rather than autonomous discovery. From the findings, implications for learners, teachers and syllabus designers, together with theoretical contributions to metalanguage and language awareness, are proposed.